Impact of Site-Neutral Payments for Commercial and Employer-Sponsored Plans - Stephen T Parente PhD (SAGE Publishing, 2024)
Site-neutral payment is a policy created by federal rule making and implemented by the Centers for Medicare and Medicaid Services (CMS) that aims to reduce healthcare costs by aligning payment rates for certain services provided in multiple care settings. Site-neutral payments are intended to eliminate the incentive for providers to acquire facilities, such as physician offices or ambulatory surgical centers (ASCs), that Medicare reimburses at the lower non-facility rate and convert those settings into hospital outpatient departments (HOPDs), where Medicare reimburses at the higher facility rate. Although initiated by Congress to address payment disparities in Medicare, similar payment discrepancies can be seen in the commercial market where individual and employer-sponsored health plans often pay more for certain outpatient services depending on their location. This analysis presents a simulation of the impact of applying site-neutral payments to the commercial market with respect to overall potential savings for consumers, health plans and the federal government. To conduct the analysis, we use an all-payer claims data base generalizable to the United States. The analysis focused on a select group of outpatient services identified by the Medicare Payment Advisory Commission (MedPAC). We mapped the MedPAC identified 68 Ambulatory Payment Classifications (APCs), the codes Medicare uses to reimburse facilities for outpatient services, to the relevant CPT4/HCPCS codes, which the commercial market uses for billing. The potential cost savings of applying the site-neutral payment policy to the commercial insurance market to be $58 billion for year 2022. We estimate the 10-year total (2024-2033) employer market premium reduction ranges from 5.35% to 5.0% and found that those premium reductions would result in employer-sponsored insurance (ESI) tax subsidy savings of $140 billion to the federal government over a 10-year period (2024-2033).